REFLECTION OF BLACK LEADERSHIP BEHAVIORS ON JOB BURNOUT OF HUMAN RESOURCES-AN APPLIED STUDY TO A SAMPLE OF BUSINESS ORGANIZATIONS IN NAJAF GOVERNORATE - Assist. Prof. Dr. Amer Abed Kareem Al-Thabhawee (American Journals, 2024)
Black leadership represents the dark picture of leadership behaviors in organizations, and these behaviors have no impact on workers and the work environment causes them to be exhausted, so the impact on organizational performance as a whole. Where the research aims to reveal the correlation and influence of the reflection of black leadership behaviors through its dimensions (petty tyranny, toxic leadership, immoral leadership, narcissistic leadership, bad supervision, destructive leadership) and the Job burnout variable through its dimensions (emotional exhaustion, depersonalization (tendency personality), weakness of personal achievement) and identified the problem of research in several questions centered on the nature of the relationship of correlation and influence between the research variables, and for this purpose, a hypothetical scheme for the research expresses two of the main hypotheses, and in order to ensure the validity of the hypotheses, all of them were subjected to multiple tests to ensure their validity. The research used the questionnaire as a means to obtain data from the researched organizations, and the research used the descriptive analytical approach as a research method. As the research community consisted of three business organizations working in the private sector in the province of Najaf, they are (Ibn Bilal National Hospital, Al-Amir National Hospital, Al-Ghadeer National Hospital), where the total community size was (130) of workers in these hospitals, and the research applied the random sample in selecting (100) employees, where the sample represented (77%) of the total research community. The data were analyzed using a set of statistical methods (Kendall's correlation coefficient, simple and multiple determination coefficient) and the results were extracted using the computer program (spss v.23). The research found results confirming the existence of a statistically significant correlation and impact between black leadership behaviors and job exhaustion of the human resource in the researched organizations.
Keywords: Black Leadership Behavior, Job burnout of Human Resources, business organizations.